1998
DOI: 10.1007/bf01345285
|View full text |Cite
|
Sign up to set email alerts
|

Locally infused taurine, GABA and homotaurine alter differently the striatal extracellular concentrations of dopamine and its metabolites in rats

Abstract: We studied in vivo the effects of locally infused taurine (50, 150, and 450 mM) on the striatal dopamine and its metabolites in comparison with those of GABA and homotaurine, a GABAA receptor agonist, in freely moving rats. The extracellular dopamine concentration was elevated maximally 2.5-, 2- and 4-fold by taurine, GABA and homotaurine, respectively. At 150 mM concentration, at which the maximum effects occurred, homotaurine increased the extracellular dopamine more than taurine or GABA. When taurine and GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Taurine, a sulphonated amino acid that has potent inhibitory effects on neuronal excitability resembling GABA acting at GABA A receptors (Huxtable, 1989), has been shown to be elevated in the NAc following acute administration of ethanol (Dahchour et al . 1994, 1996), and can modulate the extracellular levels of other neurotransmitters, including striatal dopamine (Huxtable, 1989; Ruotsalainen et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine, a sulphonated amino acid that has potent inhibitory effects on neuronal excitability resembling GABA acting at GABA A receptors (Huxtable, 1989), has been shown to be elevated in the NAc following acute administration of ethanol (Dahchour et al . 1994, 1996), and can modulate the extracellular levels of other neurotransmitters, including striatal dopamine (Huxtable, 1989; Ruotsalainen et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While PKCe null mice displayed a slight but insigni®cant decrease in dialysate levels of NE, they also displayed a signi®cant increase in dialysate levels of taurine, a ®nding that needs to be con®rmed by the no-net¯ux method (Justice, 1993;Shippenberg et al, 1999). Taurine, a sulphonated amino acid that has potent inhibitory effects on neuronal excitability resembling GABA acting at GABA A receptors (Huxtable, 1989), has been shown to be elevated in the NAc following acute administration of ethanol (Dahchour et al, 1994(Dahchour et al, , 1996, and can modulate the extracellular levels of other neurotransmitters, including striatal dopamine (Huxtable, 1989;Ruotsalainen et al, 1998). Thus, the elevated basal extracellular levels of taurine found in the NAc of PKCe ±/± mice may have a local inhibitory effect on ethanol-induced increases in extracellular dopamine levels.…”
Section: Discussionmentioning
confidence: 99%
“…More recently studies have indicated that acamprosate is a glutamatergic modulator, directly or indirectly modulating the N-methyl-d-aspartate (NMDA) receptor (Cano-Cebria´n et al, 2003a;Harris et al, 2002;Naassila et al, 1998;Popp and Lovinger, 2000;Rammes et al, 2001;Spanagel et al, 2005). Interestingly, acamprosate is a synthetically acetylated homotaurinate and several studies have demonstrated that acamprosate and homotaurine increase striatal extracellular dopamine levels (Cano-Cebria´n et al, 2003a,b;Ruotsalainen et al, 1998) and decrease EtOH intake in rats (Olive et al, 2002). However, even though several hypotheses have been forwarded, the precise molecular mechanism of action underlying the EtOH intake reducing effect of acamprosate remains unclear.…”
mentioning
confidence: 99%
“…Differently, the taurine-evoked increase in striatal dopamine was impulse-flow dependent [45]. N -Pivaloyltaurine (Figure 8) is a prodrug of taurine that is slightly converted to taurine in the brain and shown to perform the same as taurine in striatal dopamine production [46].…”
Section: Prevention Of Alzheimer’s and Neuroprotectionmentioning
confidence: 99%